Curb your enthusiasm. The complete sixth season [videorecording (DVD)] - David, Larry (HBO Home Video, 2007)
"Larry David has a pretty good life. Pretty, pretty good. He has understanding friends, a tolerant wife, and his plans for the afterlife all plotted out. See Larry take in a family of Blacks, make a generous donation, pay his respects to the dead, and befriend the handicapped. Is Larry David the most magnanimous man we know ... or the most misunderstood?"--Container.